2013
DOI: 10.1088/0022-3727/46/23/235203
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of plasma potential in a large-area pulsed dual-frequency inductively coupled discharge

Abstract: Using an emissive probe technique in 'saturated floating-potential' mode, an investigation of temporal evolution of plasma potential (V p) in a large-area pulsed dual-frequency (2 MHz/13.56 MHz) inductively coupled plasma (p-DF-CCP) is carried out. The discharge is sustained by an external type ICP antenna at a pressure of 10 mTorr in argon gas environment. The 2 MHz rf is pulsed at a frequency of 1 kHz and a duty ratio of 50%. The emissive probe is located at the centre of the substrate and 20 mm above (r = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…A similar increasing trend was also observed in the plasma potential during the pulse off-time for the time-resolved plasma potential measurement using an emissive probe. 30 …”
Section: Resultsmentioning
confidence: 99%
“…A similar increasing trend was also observed in the plasma potential during the pulse off-time for the time-resolved plasma potential measurement using an emissive probe. 30 …”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the floating potential measured by emissive probe is in good agreement with Langmuir probe measurements as explained elsewhere. 22 095101…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…56 MHz pulsing have been demonstrated. [31][32][33] In Argon discharge, pulsing 2 MHz and different combination of 2/ 13.56 MHz power levels has shown significant modulation in the plasma potential during the pulse-off phase. 31 From an estimate of electron temperature from plasma potential and floating potential measured by floating emmisive probe, it was found that the effect of increasing 2 MHz power level is to lower the electron temperature; however, increasing 13.56 MHz power increases the electron temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] In Argon discharge, pulsing 2 MHz and different combination of 2/ 13.56 MHz power levels has shown significant modulation in the plasma potential during the pulse-off phase. 31 From an estimate of electron temperature from plasma potential and floating potential measured by floating emmisive probe, it was found that the effect of increasing 2 MHz power level is to lower the electron temperature; however, increasing 13.56 MHz power increases the electron temperature. 31 Langmuir probe study under the same set-up and similar discharge conditions has predicted a slow rise in the electron density during the 2 MHz pulse-on phase in order to reach to a quasisteady state value.…”
Section: Introductionmentioning
confidence: 99%